Service Delivery and Drivers of Customer Satisfaction as Determinants of Public Relations of Food Establishments in Region XI - Viray, Aniceto Rodriguez; Montaño, Vicente Salvador Ebaño (International Journal of Management Excellence (ISSN: 2292-1648), 2017)
This study sought to determine how service delivery and drivers of customer satisfaction influence public relations of food establishments in Region XI. Using the quantitative non-experimental utilizing descriptive-correlational design, study was conducted in the different areas of Region XI. Equal distribution method was utilized in which the researcher selected 50 establishments from the different parts of Region XI that equally represented each area of the region. Quota samples of approximately 10 questionnaires were collected for each dining establishment. This study used SERVQUAL to determine the level of service delivery along with other adopted questionnaires for the other variables. The study found out that the overall level of service delivery, customer satisfaction, and public relations of dining establishments in Region XI are all moderate. Moreover, it revealed that there is a significant relationship between service delivery and customer satisfaction and public relations in dining establishments of Region XI. Finally, the indicators tangibles, empathy and assurance of service delivery and the indicators end result, timeliness, information, staff competence; staff attitude and look and feel of customer satisfaction all predict public relations in the dining establishments in Region XI.